CONTINUOUS FLUE GAS EMISIONS MONITORING SYSTEM - CASE STUDY, ROVINARI COAL –FIRED POWER PLANT - Lucica Anghelescu; Bogdan Diaconu; Mihai Cruceru (Analele Universităţii "Constantin Brâncuşi" din Târgu Jiu: Seria Inginerie, 2019)
One of the most important problems of the modern era is air pollution. About 80% of the thermo-energy groups in our country were installed during the period 1970-1980, practically exceeding their normal life span. Most of the thermo-energy capacities are not equipped with efficient installations for reducing emissions, thus the NOx and SO2 emissions are above the maximum values accepted in the EU. In the last years some thermoelectric power stations with a capacity of about 10% of the installed power have been modernized / refurbished. With Romania's accession to the European Union, it is necessary for the energy sector to comply with the regulations regarding environmental protection, the operation with pollutant emission values below the allowable limit values. These desires also lead to the use of efficient automation, data acquisition and monitoring equipment, which provide both real-time data on pollutant emissions at the thermoelectric power stations' chimneys, as well as the possibility of storing this data for further analysis. The objective of this article is to broaden the scope of knowledge regarding the systems for continuous analysis of emissions in the chimney, the need to use these systems and the performance of these systems.